2019
DOI: 10.1002/2050-7038.12057
|View full text |Cite
|
Sign up to set email alerts
|

A new method with minimum number of monitoring points for flicker source tracing by wavelet transform

Abstract: Summary Recently, both utilities and consumers have paid great attention to voltage fluctuation (flicker) problem, which is defined as low‐frequency fluctuation on the base signal of voltage. For mitigating the flicker, identification of its source is the first step. In this paper, a new method is proposed for identifying the location of flicker sources in a multi‐flicker sources power network in a more reliable and precise manner by a minimum number of monitoring points. This method is based on the wavelet tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Then, the exact location of the flicker source is identified using the amount of voltage flickers determined in the fifth step (calculating the contribution) and comparing them together. Considering that in tracing the location of flicker source using method 37 the relative error is less than the maximum allowable relative error ( E r‐max ), it can be concluded that using the data of only five monitoring points the proposed method in this article and Reference 37 can detect the exact location of the flicker source. The value of E r‐max depends on the identified location of the flicker source using the method, in Reference 37 and if the relative error is less than E r‐max , the location of the flicker source has been successfully traced.…”
Section: Simulation Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Then, the exact location of the flicker source is identified using the amount of voltage flickers determined in the fifth step (calculating the contribution) and comparing them together. Considering that in tracing the location of flicker source using method 37 the relative error is less than the maximum allowable relative error ( E r‐max ), it can be concluded that using the data of only five monitoring points the proposed method in this article and Reference 37 can detect the exact location of the flicker source. The value of E r‐max depends on the identified location of the flicker source using the method, in Reference 37 and if the relative error is less than E r‐max , the location of the flicker source has been successfully traced.…”
Section: Simulation Resultsmentioning
confidence: 92%
“…If the flicker source location, traced by the method in Reference 37 is between the busbar n and the point y , the flicker source location is considered to be on busbar n ; otherwise, it is considered to be on busbar n + 1. Therefore, the maximum allowable relative error is equal to half the distance between busbars n and n + 1 divided by the flicker source distance ( d ).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations